THE EAST ASIA-AFRICA RELATION DYNAMICS: THE IMPLICATIONS OF PRC-NIGERIA ECONOMIC COOPERATION THROUGH (FOCAC) FOR REGIONAL DEVELOPMENT PROGRESS - Darynaufal Mulyaman; Yafet Wibowo Gegeh Aronta Sitepu; Raden Ariobimo Bayu Sontany (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
This paper reviews the form of cooperation and the implications of economic cooperation between the People's Republic of China (PRC) and Nigeria, in the economic field within the framework of the Forum on China Africa Cooperation (FOCAC). The theory used is the theory of International Cooperation according to K.J. Holsti. the author will look specifically at what are some of Nigeria's abundant wealth that should be utilized and how it has implications for the Nigerian economy and the author will also look at how the region building in Africa is in political and economic challenges. The purpose of writing this paper is to find out how cooperation takes shape and the implications of PRC-Nigeria economic cooperation through the Forum on China Africa Cooperation. The author also argues that China also has a national interest in Nigeria. The author also sees the economic implications for Nigeria as important to encourage Nigeria and the African region in general.